Auricular pressure as an adjuvant treatment for type 2 diabetes: data mining and meta-analysis - Yu, Yunfeng; Xiang, Qin; Liu, Xiu; Yin, Yuman; Bai, Siyang; Yu, Rong (Frontiers in Endocrinology, 2024)
Objective: This study aimed to explore the clinical efficacy and acupoint combinations of auricular pressure for treating type 2 diabetes. Methods: Eight common databases were searched for publications related to auricular pressure in type 2 diabetes as of November 2023. A meta-analysis was performed to assess the efficacy and safety of auricular pressure therapy. Data mining was used to analyze the core acupoints for auricular pressure. Results: Meta-analysis demonstrated that compared with the conventional treatment group, the combined auricular pressure and conventional treatment group had significantly reduced fasting blood glucose (mean difference [MD]: -0.93; 95% confidence interval [CI]: -1.17 to -0.68; p < 0.00001), 2-hour postprandial blood glucose (MD: -1.58; 95% CI: -2.04 to -1.12; p < 0.00001), glycated hemoglobin A1c (MD: -0.83; 95% CI: -1.19 to -0.48; p < 0.00001), total cholesterol (MD: -0.43; 95% CI: -0.72 to -0.14; p = 0.004), triglycerides (MD: -0.33; 95% CI: -0.64 to -0.03; p < 0.00001), systolic blood pressure (MD: -14.75; 95% CI: -24.46 to -5.05; p = 0.003), diastolic blood pressure (MD: -10.32; 95% CI: -20.14 to -0.50; p = 0.04), and body mass index (MD: -1.74; 95% CI: -2.61 to -0.87; p < 0.0001), while adverse events were comparable (RR: 0.84; 95% CI: 0.43 to 1.66; p = 0.61). Egger's test revealed no publication bias (p = 0.715). Data mining identified AH6a, TF4, AT4, CO18, and CO10 as core acupoints for treating type 2 diabetes with auricular pressure. Conclusion: Auricular pressure safely improves blood glucose and lipid levels, blood pressure, and body mass index in patients with type 2 diabetes. A regimen consisting of AH6a, TF4, AT4, CO18, and CO10 is expected to serve as a complementary treatment for type 2 diabetes.